KOORDINASI PIHAK KECAMATAN DENGAN KEPOLISIAN SEKTOR KECAMATAN KUANTAN MUDIK DALAM PENEGAKAN HUKUMPERTAMBANGAN TANPA IZIN (PETI) DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI TAHUN 2014-2016 - Herwansyah Putra; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Illegal mining (Pertambangan Emas Tanpa Izin) is a serious problem. So that the law enforcement of illegal mining in Kuantan Mudik Sub-district requires the integration of the resource or involves many elements in Kuantan Mudik Sub-district. Many things had done in the term of law enforcement of illegal mining by the Sub-District Government Side and Sub-District Police in Kuantan Mudik Sub-district. The problems in thisresearch are (1)How is the implementation of the coordination Sub-District Government Side with Sub-District Police in the term of law enforcement of illegal miningin Kuantan Mudik Sub-district in 2014-2016. (2) What are the reasons that cause the implementation of the coordination Sub-District Government Side with Sub-District Police in the term of law enforcement of illegal miningin KuantanMudik Sub-district in 2014-2016 become not optimally done?The purpose of this research is describing the coordination Sub-District Government Side with Sub-District Police in the term of law enforcement of illegal mining in Kuantan Mudik Sub-district in 2014-2016. The research method is qualitative method with phenomenology approach.The conclusion of this research mentions that the implementation of the coordination betweenSub-District Government Side with Sub-District Police in the term of law enforcement of illegal miningin Kuantan Mudik Sub-district in 2014-2016 has been being good enough. Although, the intensity to implement the coordination still needs the optimalization. The author hopes the result of this result can help to enrich the information of the coordination in law enforcement of illegal mining in Kuantan Singingi Regency especially in Kuantan Mudik Sub-district.Keywords: Coordination, sub-district government side with sub-district police of KuantanMudik, law enforcement of illegal mining (PETI)